Hubungan Self Regulated Learning (SRL) dengan Motivasi Belajar IPAS Siswa Kelas V SD Inpres 6/75 Manurunge Kecamatan Tanete Riattang Kabupaten Bone - sitti jauhar; muhammad idris jafar; muhammad ikram (MACCA : Science-Edu Journal, 2026)
This study aims to determine the relationship between Self Regulated Learning (SRL) and motivation to learn science (IPAS) among fifth-grade students at SD Inpres 6/75 Manurunge, Tanete Riattang District, Bone Regency. This research employed a quantitative approach with a correlational research design. The population consisted of 57 fifth-grade students, all of whom were included as research samples. Data were collected using SRL and learning motivation questionnaires. The data analysis techniques used were descriptive statistics and inferential statistics with Spearman correlation test. The descriptive analysis results showed that the average SRL score was 89.49 and the average learning motivation score was 89.63, both categorized as high. Inferential analysis showed that rcount > rtable (0.620 > 0.261) at a 5% significance level. Therefore, it can be concluded that there is a positive and significant relationship between Self Regulated Learning (SRL) and motivation to learn science among fifth-grade students at SD Inpres 6/75 Manurunge.